Sociological factors as predictors of academic emotion among Nigeria university students (2013)
This study investigated the sociological factors as predictors of academic emotion among Nigeria University students. The study adopted a survey research design. The participants in the study were 345 undergraduates in South-West, Nigeria. Their age ranged between 17 years and 24 years with mean age of 21.69 years. Three valid and reliable instruments were used to assess academic emotion, parental involvement and social support while birth order was assessed by requesting the participants to fill out a short family history form as part of a battery of sociological tests. Descriptive statistics, Pearson’s Product Moment Correlation and multiple regression analysis were used to analyse the data. The result revealed that parental involvement, social support and birth order were potent predictors mildly associated to academic emotion. The study has implications for behaviour therapist, educational psychologists, educational stakeholders, government and parents on how challenges faced by student under a serious emotional strain which are virtually involved in every aspect of teaching and learning process can be reduced and well managed.